Comparative study of the effectiveness of two different dosage of sublingual misoprostal for cervical ripening before hysteroscopy - Jadon, Komal; Chawla, Indu; Kumari, Kanika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: Hysteroscopy a minimally invasive approach for evaluating uterine cavity, and has become an indispensable diagnostic and therapeutic procedure. The main limiting factor while performing office hysteroscopy is the level of pain or discomfort encountered during the procedure. The pain is attributed mainly to the difficulty in entering the internal cervical os with the hysteroscope and while distending uterine cavity. It could be reduced if cervix is ripened before the procedure. The purpose of this prospective observational study was to compare the effectiveness, adverse effects and surgery-related complications associated with two different doses of sublingual Misoprostol (100 and 200 µg) given 2-4 hours before hysteroscopy. Methods: A randomised comparative study was conducted in the department of Obstetrics and Gynaecology of ABVIMS and Dr. RML hospital New Delhi, from 1st November, 2018 to 31st March, 2020. One hundred and twenty women, fulfilling inclusion criteria were subjected to hysteroscopy. Women received either 100 µg (Group I) or 200 µg (Group II) of sublingual Misoprostol 2-4 hours prior to hysteroscopy. The primary outcome of the study was cervical dilatation as measured by the largest number of Hegar dilator that could be inserted without resistance at the beginning of procedure. The largest dilator that negotiated cervical canal without resistance at the beginning of procedure was recorded as the baseline cervical width. The secondary outcomes were subjective assessment of the surgeon of the ease of dilatation of cervix and adverse effects of drug (i.e. vaginal bleeding, shivering, fever and pain as measured on visual analog scale). Results: The mean baseline cervical width as measured by first Hegar dilator that could be passed through the cervical canal without resistance was 6.6±0.62 mm in group I and 6.94±1.21 mm in group II respectively (p value=0.016). Adverse effects like vaginal bleeding, shivering was more in group II compared to group I. No statistically significant difference was found between group I and II with regards to visual analog scale. Conclusions: 100 µg Misoprostol can be used for cervical ripening prior to hysteroscopy with minimal adverse effects.